Progressive aortic root dilatation in pediatric heart transplant recipients. Issue 7 (23rd June 2017) - Sachdeva, Shagun; Zhang, Liyun; Simpson, Pippa; Frommelt, Peter C.
Abstract : Background: To determine prevalence, clinical implication, and risk factors for aortic root dilation (ARD) in pediatric heart transplant recipients. Methods: Serial echocardiograms were reviewed in all pediatric heart transplant recipients from 1999 to 2014 to assess maximal systolic diameter at the aortic annulus, aortic sinus, aortic sino‐tubular (ST) junction, and ascending aorta. ARD was defined by a sinus/annulus ratio >1.56, ST junction/annulus ratio >1.28,  and/or ascending aorta/annulus ratio >1.35. Results: A total of 147 subjects (53% male) were evaluated; 50% had congenital heart disease (CHD). Of the 74 with CHD, 38 had prior aortic arch reconstruction. The median age at transplant was 3 years (7 days–20.3 years) with a median duration of follow‐up of 3.88 years (3 months–15 years). Prevalence of ARD significantly increased in the cohort from 15.6% at the initial echocardiogram to 49.6% at later follow‐up ( P <.0001). The median duration to development of ARD was 7.6 months. There were no significant differences in prevalence of ARD or days to maximum ratio based on the pretransplant diagnosis. Aortic regurgitation was very rare (7 with ≤mild) and did not correlate with ARD or require any interventions. Conclusion: During intermediate follow‐up, ARD commonly develops in children post–heart transplant, and prevalence increases with time after transplant. Within 1 year after transplant, almost 50% had developed abnormalities in aortic root size that were not apparent at the initial posttransplant echocardiogram. Preexisting CHD or need for prior arch reconstruction did not increase the risk of ARD.